1991
DOI: 10.1111/j.1432-1033.1991.tb16165.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ganglioside GM3 and its breakdown products on lymphoblastic transformation and T‐suppressor activity

Abstract: The influence of ganglioside GM3 and some of its breakdown products on phytohemagglutinin‐induced blast transformation of human lymphocytes and concanavalin‐A‐induced T‐suppressor activity was studied. The structures of two major hydrolysis products of GM3 were established by negative‐ion fast‐atom‐bombardment mass spectrometry as neuraminyllactosylsphingosine (NeuLacSph) and neuraminyllactosylceramide (NeuLacCer). Both substances were shown to be potent inhibitors of mitogen‐induced lymphoblastic transformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Ganglioside GM3 inhibited growth stimulation by fibro blast growth factor [1], regulated receptor function of epi dermal growth factor [2] and integrin receptor function [3,4], Concerning the effect of the modulation of immune function, ganglioside GM3 showed an inhibitory effect on natural killer cytotoxicity and an enhancement of T sup pressor cell activity [5,6], Moreover, suppresion of interleu kin-2 (IL-2) activity and inhibition of IL-2-and interleu kin-4 (IL-4)-dependent T cell proliferation were observed by the addition of exogenous GM3 [7][8][9]. Thus, these things suggested that GM3 may play a role in the regulation of T lymphocyte functions.…”
Section: Introductionmentioning
confidence: 99%
“…Ganglioside GM3 inhibited growth stimulation by fibro blast growth factor [1], regulated receptor function of epi dermal growth factor [2] and integrin receptor function [3,4], Concerning the effect of the modulation of immune function, ganglioside GM3 showed an inhibitory effect on natural killer cytotoxicity and an enhancement of T sup pressor cell activity [5,6], Moreover, suppresion of interleu kin-2 (IL-2) activity and inhibition of IL-2-and interleu kin-4 (IL-4)-dependent T cell proliferation were observed by the addition of exogenous GM3 [7][8][9]. Thus, these things suggested that GM3 may play a role in the regulation of T lymphocyte functions.…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence on the dependence of the suppressive effect on the ganglioside structure is still incomplete and frequently contradictory. This led us to undertake a systematic study of the influence of various gangliosides on the response of lymphocytes to the action of the plant-derived mitogen phytohemagglutinin [12][13][14].…”
Section: Gangliosides and Lymphoblastic Transformationmentioning
confidence: 99%
“…The disialogangliosides GD3 and GDla and the glucosamine-containing ganglioside IV3NeuAc-nLc4Cer displayed a strong inhibitory effect whereas the monosialogangliosides GMI and GM3 had only very weak if any influence on the induction of lymphocytic blast transformation by the mitogen (Cer = ceramide; Neu = neuraminic acid; Sph = sphingosine). At the same time, however, some breakdown products of GM3 (its de-Nacetyl and de-N-acetyl-de-N-acyl derivatives NeuLacCer and NeuLacSph) significantly inhibited Glycosphingolipid concentration = 50 nmol/ml phytohemagglutinin-stimulated thymidine incorporation at very low concentrations [14]. This effect was not due to cytotoxic or cytostatic action of the gangliosides, and their direct interaction with phytohemagglutinin seemed to be excluded as inhibitory mechanism because significant inhibition was seen already at ganglioside :mitogen molar ratios of 1:15 or less [12,13].…”
Section: Gangliosides and Lymphoblastic Transformationmentioning
confidence: 99%
See 2 more Smart Citations